Análisis al impuesto a la salida de divisas ISD y su efecto en la inversión extranjera directa IED período 2012-2018 - Barragán Moreano, Daniela Dennys (2020)
In 2008, the Foreign Currency Outflow Tax was born, it was promulgated through the Reform Law for Tax Equity in Ecuador (LRET), in order to regulate capital flight. The objective of this qualification work is to analyze whether the application of said tax had an impact on Foreign Direct Investment (FDI) during the 2012-2018 period, which has a statistical evaluation of the collection capacity it has and the economic outlook …….. of foreign currency, the accreditation or deposit, check amount, transfer or money order abroad with or without the intermediation of institutions of the financial system, in other words, these were the generating facts (SRI, 2020). The tax was initially 1% and later 2%..............